Comparative transcriptional analyzes of Xanthomonas citri subsp. citri reveal mechanisms of adaptation and bacterial virulence in the early stage of citrus canker disease - Suárez-Acevedo, Sara; Chaves-Bedoya, Giovanni; Guariz-Pinheiro, Daniel [UNESP]; Cristina-Lopes, Aline [UNESP]; Mari-Murata, Mayara [UNESP]; Hirochi-Herai, Roberto; Aparecido-Ferro, Jesus [UNESP]; Rodas-Mendoza, Elkin (My University, 2022)
Xanthomonas citri subsp. citri (Xac) is the causal agent of citrus canker, a disease that affects citrus crops of economic importance. Sweet orange cultivars “Pera Rio” (Citrus sinensis) are intermediate susceptible to the disease, while acid lime ‘Galego’ (Citrus aurantifolia) are highly susceptible. To understand the molecular mechanism underlying the differences in Xac response when infecting these two citrus genotypes, in vivo transcriptomic profiles of Xac infecting both genotypes were compared using high throughput sequencing of RNA. Bioinformatics analysis detected 839 and 982 differentially expressed genes (DEGs) in Xac during their interaction with sweet orange and acid lime compared to controls, respectively. Moreover, 607 DEG genes were found to be common in both genotypes. In both hosts, the annotation of DEGs showed that Xac induced genes involved with the Type III Secretion System and corresponding effector genes, cell wall degrading enzymes, and xanthan gum synthesis. In addition, higher expression values in Xac genes associated with oxidative stress resistance were found in their interaction with sweet orange, compared to acid lime. The results collectively allow the proposition of the main genetic modulation mechanism used by Xac to develop the disease in the early stages of host infection and reveal different transcriptional responses when the bacteria interact with C. sinensis and C. aurantifolia. Thus, our study provides information about the intercellular environment of Xac and the possible strategies it uses to promote the disease.
Keywords: Differentially expressed genes; RNA-Seq; Sweet orange; Xanthomonas citri